Assessing smallholder farmers’ motivation to adopt agroforestry using a multi-group structural equation modeling approach - Buyinza, J.; Nuberg, I.K.; Muthuri, Catherine W.; Denton, M.D. (Springer, 2020)
This study applied the multi-group structural equation modeling technique to identify differences in farmer motivations to adopting agroforestry practices in the Mt. Elgon region of Uganda. Data were collected from interviews with 400 smallholder coffee farmers belonging to four categories which included: (1) those actively participating in an Australian-funded trees for food security (T4FS) project from phase 1 (2014); (2) farmers neighbouring those actively participating in the T4FS project; (3) farmers actively participating in the T4FS project from phase 2 (2017) and; (4) farmers living distant and unaware of the T4FS project. We used the theory of planned behaviour framework to assess the adoption behaviour of these farmer categories resulting from project interventions. About 40% of the variation in farmer motivation to integrate trees in their coffee plantations was explained by the significant variables of ‘attitude’ and ‘perceived behavioural control’ among farmers actively participating in the T4FS project from phase 1. However, the neighbors of participating farmers and farmers who had never interacted with the project were only motivated by ‘attitude’ and ‘social norms’ respectively. Farmer motivation resulting from social pressure was strongest among farmers who had never interacted with the project, and in the absence of project interventions, rely on existing social structures to drive change in their community. Farmers’ perceived behavioural control to overcome tree planting barriers and their attitude to the economic benefits of shaded coffee were significantly different among the four farmer categories (p < 0.05). The findings indicate that psychological factors are key drivers to the farmers’ internal decision-making process in agroforestry technology adoption and can be context-specific. The adoption behaviour of smallholder farmers is mainly shaped by existing community social norms and beliefs that tend to promote knowledge exchange, as opposed to the conventional knowledge transfer extension approaches. Norms are therefore an inherent part of social systems and can create distinct farming practices, habits and standards within a social group. Researchers and extension agents can act upon these identified positive attitudes, norms and perceived behavioural controls to guarantee adoption and sustainability of agricultural technologies.